SECURITIZATION OF ILLEGAL IMMIGRANTS ON THE SOUTH BORDER OF THE UNITED STATES BY PRESIDENT DONALD TRUMP: FOREIGN POLICY CHANGES - Aldelita Putri Balqis Romulia (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
The United States is a country that implements a free and most open immigration foreign policy in the world as evidenced by the acceptance of hundreds of thousands of regional and international immigrants each year. The government that is given the responsibility to lead the country will give priority to immigration issues to be formulated in foreign policy. In the era of President Donald Trump, the issue of immigrants was focused on solving the problem of illegal immigrants at the Southern border with an America First approach and securitization measures. This research will focus on the factors that became the basis for President Donald Trump's consideration of securitization in order to change United States immigration policies, using the framework of The Politics of Foreign Policy Change, namely the identification of global and domestic conditions with political and economic elements as factors that underlying changes in a country's foreign policy. This study argues that President Trump's securitization actions in the context of changing US immigration policy are based on global political conditions, namely the presence of transnational crimes such as identity fraud, drug smuggling, and criminal acts. Global economic conditions, related to immigrants with low wages undermine the standard minimum wage for American workers. Political domestic factors are related to the fulfillment of President Trump's campaign promise to protect the homeland and people of the United States from the threat of illegal immigrants on the southern border. Domestic economic factors are related to American jobs which are occupied by illegal immigrants by falsifying their identities at companies and impacting the loss of the right to social security for United States citizens. Keywords: Foreign Policy Changes, Immigration Policy, Securitization.